The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1161/atvbaha.112.300523
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Soluble Receptor for Advanced Glycation End Products in Stroke

Abstract: Objective-Little is known about the involvement of the soluble form of receptor for advanced glycation end products (sRAGE) in acute ischemic stroke (IS). Here, we aim to identify the role of plasma sRAGE and high mobility group box 1 (HMGB1) in imaging-confirmed IS patients, as well as mice subjected to focal ischemic stroke. Methods and Results-IS patients were recruited and plasma samples were collected for the measurement of sRAGE and HMGB1 after stroke. The relation of sRAGE and HMGB1 with acute IS was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 52 publications
2
75
1
1
Order By: Relevance
“…12,20,[30][31][32][33] We have recently established that plasma levels of HMGB1 as well as interactions between HMGB1 and RAGE were increased significantly after ischemic stroke onset both in human and mice. 14 We also found that administration of recombinant sRAGE effectively protects mice from ischemic reperfusion injury and protects primary neurons from energy deprivation-induced cell death via a mechanism involving reduced RAGE-associated inflammatory pathways. 14 The present study showed that CSF levels of HMGB1 increased significantly in SAH patients, and the values were positively correlated with outcome even after adjustment for clinical variables.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…12,20,[30][31][32][33] We have recently established that plasma levels of HMGB1 as well as interactions between HMGB1 and RAGE were increased significantly after ischemic stroke onset both in human and mice. 14 We also found that administration of recombinant sRAGE effectively protects mice from ischemic reperfusion injury and protects primary neurons from energy deprivation-induced cell death via a mechanism involving reduced RAGE-associated inflammatory pathways. 14 The present study showed that CSF levels of HMGB1 increased significantly in SAH patients, and the values were positively correlated with outcome even after adjustment for clinical variables.…”
Section: Discussionmentioning
confidence: 66%
“…14 We also found that administration of recombinant sRAGE effectively protects mice from ischemic reperfusion injury and protects primary neurons from energy deprivation-induced cell death via a mechanism involving reduced RAGE-associated inflammatory pathways. 14 The present study showed that CSF levels of HMGB1 increased significantly in SAH patients, and the values were positively correlated with outcome even after adjustment for clinical variables. In addition, RAGE expression increased in cultured neurons exposed to post-SAH CSF.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The differences of sRAGE levels among different stroke subtypes could be related to acute stroke severity rather than different etiologies of the stroke subtypes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous administration of sRAGE may capture and eliminate circulating RAGE ligand, thus acting as a decoy receptor and protecting against tissue damage. Systemic administration of sRAGE may be an effective therapeutic approach for all RAGE-mediated vascular disorders [23].…”
Section: Discussionmentioning
confidence: 99%